2014
DOI: 10.1002/anie.201404136
|View full text |Cite
|
Sign up to set email alerts
|

Pure In‐Phase Heteronuclear Correlation NMR Experiments

Abstract: A general NMR approach to provide pure in-phase (PIP) multiplets in heteronuclear correlation experiments is described. The implementation of a zero-quantum filter efficiently suppresses any unwanted anti-phase contributions that usually distort the multiplet pattern of cross-peaks and can hamper their analysis. The clean pattern obtained in PIP-HSQMBC experiments is suitable for a direct extraction of coupling constants in resolved signals, for a peak-fitting process from a reference signal, and for the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 26 publications
0
62
0
Order By: Relevance
“…S8 in the SI). In this PIP-HSQMBC-TOCSY experiment, pure in-phase (PIP) signals are obtained, as previously reported for related HSQC-TOCSY [10] and PIP-HSQMBC [29] experiments. This can be particularly useful when determining n J(CH) coupling constants along the detected dimension.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…S8 in the SI). In this PIP-HSQMBC-TOCSY experiment, pure in-phase (PIP) signals are obtained, as previously reported for related HSQC-TOCSY [10] and PIP-HSQMBC [29] experiments. This can be particularly useful when determining n J(CH) coupling constants along the detected dimension.…”
Section: Resultsmentioning
confidence: 66%
“…In the case of non-resolved multiplets, n J(CH) can be extracted comparing linewidths in coupled/decoupled spectra [7]. In contrast to the PIP-HSQMBC experiment [29], a PIP-HSQMBC-TOCSY cross-peak can be the cumulative result of several and different coupling pathway contributions. This would preclude the extraction of n J(CH) using the IPAP methodology or the determination of the relative sign as reported for selective HSQMBC versions [23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…We have found that the PIP‐HSQMBC 13 and IPAP‐HSQMBC 14 pulse sequences permit facile determination of 1 H‐ 15 N coupling constants of a variety of oximes, hydrazones and thio derivatives of oximes. The advantages of the two pulse sequences have been detailed in the relevant publications . It is sufficient to note that in systems where the protons of interest are singlets or the 1 H‐ 1 H coupling is less than the 1 H‐ 15 N coupling to be measured, the coupling constant can be measured directly from the PIP‐HSQMBC .…”
Section: Resultsmentioning
confidence: 99%
“…Advances in spectrometer and probe technology now allow routine measurement of 1 H‐ 15 N coupling to be accomplished using a variety of techniques . Specifically, variants of the HSQMBC pulse sequence have been proven to be especially useful . In addition, we recently introduced a new pulse sequence for measurement of 13 C‐ 15 N coupling at natural abundance, the HCNMBC experiment .…”
Section: Introductionmentioning
confidence: 98%
“…Examples include a variant of the F1‐coupled J ‐scaled HSQC with insertion of a HMQC‐like evolution block, the P.E. HSQC – both relying on the well known E.COSY experiment, which may also applied to measure n T HH – and the PIP–HSQC . Reliable coupling extraction from general COSY‐type spectra is often impossible because of broad lines, large couplings and signal overlap.…”
Section: Measurement Of Residual Dipolar Couplingsmentioning
confidence: 99%